2005
DOI: 10.1021/jp0456178
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic Electron Affinities of the Polyhydrated Adenine−Thymine Base Pair:  A Density Functional Study

Abstract: Adiabatic electron affinities (AEAs) of the adenine-thymine (AT) base pair surrounded by 5 and 13 water molecules have been studied by density functional theory (DFT). Geometries of neutral AT x nH2O and anionic (AT x nH2O)- complexes (n = 5 and 13) were fully optimized, and vibrational frequency analysis was performed at the B3LYP/6-31+G** level of theory. The optimized structures of the neutral (AT x nH2O) and (AT x nH2O)- complexes were found to be somewhat nonplanar. Some of the water molecules are displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
2

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 109 publications
6
42
0
2
Order By: Relevance
“…Using the above-mentioned approaches, the electron affinities of DNA bases and base pairs have been studied in a number of publications in recent years. 70,[89][90][91][92][93][94][95][96][97][98] Using B3LYP/DZPþþ level of theory, Schaefer and co-workers [90][91][92] calculated the electron affinities of T, C, and U in the presence of 1-5 waters and their calculated ZPE-corrected absolute electron affinities of T, U, and C with 5 waters were calculated to be 0.65, 0.74, and 0.61 eV. [90][91][92] respectively.…”
Section: Gase-phase Electron Affinities Of Dna Bases and Base Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the above-mentioned approaches, the electron affinities of DNA bases and base pairs have been studied in a number of publications in recent years. 70,[89][90][91][92][93][94][95][96][97][98] Using B3LYP/DZPþþ level of theory, Schaefer and co-workers [90][91][92] calculated the electron affinities of T, C, and U in the presence of 1-5 waters and their calculated ZPE-corrected absolute electron affinities of T, U, and C with 5 waters were calculated to be 0.65, 0.74, and 0.61 eV. [90][91][92] respectively.…”
Section: Gase-phase Electron Affinities Of Dna Bases and Base Pairsmentioning
confidence: 99%
“…In another study, AEA of the thymidine monophosphate-adenine (5 0 -dTMPH-A) pair was calculated using the PCM model and the B3LYP/DZPþþ method as 2.05 eV, 93 while the AEA of an AT base pair in the presence of 13 waters was predicted to be 0.97 eV at B3LYP/6-31þG Ã level of theory. 97 In a recent study, 98 the EA of GC base pair was also calculated using B3LYP/6-31þG…”
Section: Gase-phase Electron Affinities Of Dna Bases and Base Pairsmentioning
confidence: 99%
“…Further, both the specific and bulk solvent effects should be combined to treat the solvent effect properly [34][35][36][37]. Here, we have included three water molecules to treat the specific solvent effect of water followed by the treatment of bulk solvent effect of water using the IEF-PCM [25].…”
Section: Table IIImentioning
confidence: 99%
“…Several theoretical and experimental investigations were also performed to determine the electron affinity, ionization potential and protonation and deprotonation properties of purine and pyrimidine bases and base pairs [88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103]. Based on the experimental and theoretical data, the adiabatic valence electron affinity for pyrimidine bases has been estimated to be in the range 0-0.2 eV, while those for adenine and guanine amount to about À0.35 and À0.75 eV respectively [88].…”
Section: Ground-state Structures Of Nucleic Acid Bases and Base Pairsmentioning
confidence: 99%
“…Schaefer and coworkers [101] have recently investigated the structures and properties of deprotonated GC base pairs. Kumar et al [102,103] have recently investigated the adiabatic electron affinities of GC, AT and hypoxanthine-cytosine base pairs at the DFT level. These authors have found that polyhydration leads to significant increase in the electron affinity of the AT base pair.…”
Section: Ground-state Structures Of Nucleic Acid Bases and Base Pairsmentioning
confidence: 99%